2020
DOI: 10.1016/j.ajog.2020.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of severe acute respiratory syndrome coronavirus 2 invading the human placenta using electron microscopy

Abstract: This area was used for transmission electron microscopy.Algarroba. Visualization of SARS-CoV-2 invading the human placenta using electron microscopy. Am J Obstet Gynecol 2020.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
188
0
13

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(221 citation statements)
references
References 7 publications
(9 reference statements)
9
188
0
13
Order By: Relevance
“…Algarroba et al showed potential viral transmission in the placenta by identifying coronavirus virions in placental villi using electron microscopy, but the newborn was COVID-19 RT-PCR negative and asymptomatic. 25 So, from these limited data we agree with Mimouni et al that vertical transmission from maternal infection to fetus probably occurs rarely. 54 Currently, AAP recommends testing the Algarroba et al 25 1 0…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Algarroba et al showed potential viral transmission in the placenta by identifying coronavirus virions in placental villi using electron microscopy, but the newborn was COVID-19 RT-PCR negative and asymptomatic. 25 So, from these limited data we agree with Mimouni et al that vertical transmission from maternal infection to fetus probably occurs rarely. 54 Currently, AAP recommends testing the Algarroba et al 25 1 0…”
Section: Discussionsupporting
confidence: 89%
“…25 So, from these limited data we agree with Mimouni et al that vertical transmission from maternal infection to fetus probably occurs rarely. 54 Currently, AAP recommends testing the Algarroba et al 25 1 0…”
Section: Discussionsupporting
confidence: 89%
“…Conversely, the rising expression of TMPRSS2 with age in both the conducting airways and alveolar epithelium may explain the increased susceptibility to symptomatic infection and severe ARDS observed in adults relative to children. To date, there have been very few cases of vertical transmission of SARS-CoV-2 to newborns 22 , despite viral particles being identified in the placentas of women who were infected with SARS-CoV-2 23 . In light of the very low expression of ACE2 in ciliated epithelial cells, our data raise the possibility Figure 3.…”
Section: Secretory Cells Ciliated Cells At2 Cells At1 Cellsmentioning
confidence: 99%
“…Zeng and colleagues reported the outcome of 33 neonates born to mothers with COVID-19 nding despite implementing strict infection control measures 3 neonates (9%) presented with early onset SARS-CoV-2 infection 7 . Transplacental transmission is feasible as virions invading syncytiotrophoblast in placental villi have been documented by electron microscopy 8 No speci c clinical nding has been described in newborns, but severe neonatal infections are possible. Variable body temperature, respiratory symptoms (cough, tachypnea, apnea, grunting, nasal aring), tachycardia, lethargy, vomiting, diarrhea, and abdominal distention have been described.…”
Section: Discussionmentioning
confidence: 99%